PENGARUH MEDIA SOSIAL DAN e-WOM TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PRODUK UMKM MAKANAN AYAM GEPREK DI KOTA PEKANBARU - Satryawan Edo; Nursanti Aida; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Social Media and e-WOM onpurchasing decisions through interest in buying UMKM Ayam Geprek productsin the city of Pekanbaru. The population in this study was the entire Pekanbarucommunity who knew, had used or were currently buying UMKM Ayam Geprekproducts, both men and women, totaling 105 people. Primary data was collectedby using a questionnaire as an instrument to prove the results of the study, to testthe hypothesis in this study using path analysis (path analysis) with the help of theSPSS program. The sampling technique that has been selected is the NonProbality Sampling technique where sampling is carried out on the basis ofcertain objectives or considerations. The results of this study indicate that: 1)there is a positive and significant effect of Social Media on interest in buyingUMKM Ayam Geprek products in the city of Pekenbaru, 2) there is a positive andsignificant effect on e-WOM on interest in buying UMKM Ayam Geprek productsin the city of Pekanbaru, 3) there is a positive influence and significant SocialMedia on purchasing decisions for UMKM Ayam Geprek products in the city ofPekanbaru, 4) there is a positive and significant influence on e-WOM onpurchasing decisions for UMKM Ayam Geprek products in Pekanbaru City, 5)there is a positive and significant influence on buying interest on purchasingdecisions for UMKM Ayam Geprek products in Pekanbaru City, 6 ) there is apositive and significant effect of Social Media on purchasing decisions throughbuying interest as an intervening variable for UMKM Ayam Geprek products inthe city of Pekanbaru, 7) there is a positive and significant influence on e-WOMon purchasing decisions through buying interest as an intervening variable forUMKM Ayam Geprek products in the city of Pekanbaru. Keywords: Social Media, e-WOM, Purchase Interest, and Purchase Decision.